1996
DOI: 10.1126/science.274.5284.90
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Homolog of Hepatitis Delta Antigen: Implications for Viral Replication and Evolution

Abstract: Hepatitis delta virus (HDV) is a pathogenic human virus whose RNA genome and replication cycle resemble those of plant viroids. However, viroid genomes contain no open reading frames, whereas HDV RNA encodes a single protein, hepatitis delta antigen (HDAg), which is required for viral replication. A cellular gene whose product interacts with HDAg has now been identified, and this interaction was found to affect viral genomic replication in intact cells. DNA sequence analysis revealed that this protein, termed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 40 publications
1
100
1
2
Order By: Relevance
“…Although speculative, our findings would theoretically point to at least some 'HCV DNA sequences' being part of a system like human endogenous DNA sequences. This would be similar to a situation comparable with that of the cellular homologue for hepatitis delta antigen (17) or the endogenous retroviral related sequences, HERV (18). The virus-like particles occasionally found in 'HCV infected' cells (19) would not contradict the findings presented here: e. g., virus-like particles originated from endogenous retroviral related sequences can also be found (20).…”
Section: Discussionsupporting
confidence: 47%
“…Although speculative, our findings would theoretically point to at least some 'HCV DNA sequences' being part of a system like human endogenous DNA sequences. This would be similar to a situation comparable with that of the cellular homologue for hepatitis delta antigen (17) or the endogenous retroviral related sequences, HERV (18). The virus-like particles occasionally found in 'HCV infected' cells (19) would not contradict the findings presented here: e. g., virus-like particles originated from endogenous retroviral related sequences can also be found (20).…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies showed location of TCF/LEF family and CCDC85B in the nucleus (Brazas and Ganem, 1996;Willert and Nusse, 1998). These reports suggest that CCDC85B may interact with TCF/LEF family.…”
Section: Ccdc85b Interacts With Tcf4 In the Nucleusmentioning
confidence: 64%
“…NM_006848) was increased in Ad-p53-infected Saos-2 cells. The physiological role of CCDC85B is not exactly clear (Brazas and Ganem, 1996).…”
Section: Ccdc85b Is Upregulated By P53mentioning
confidence: 99%
“…The rolling circle mechanism for HDV replication during which multimeric intermediate transcripts are synthesized requires intact circular RNA template for transcription (Branch & Robertson, 1984;Chen et al+, 1986)+ Transcription reaction detected in our in vitro system depends on a specific cleavage of the RNA template, implying that it cannot directly represent the initiation step of HDV RNA replication+ However, initiation of the rolling circle replication involving a similar mechanism is possible by considering a hypothesis of the RNA template switching+ According to this model, pol II would cleave one molecule of HDV RNA and proceed into the elongation phase only after switching to another circular template, using the cleaved template as a primer for initiation of replication+ In fact, the use of primers to initiate replication is a common theme among the viruses+ For example, tRNAs (Gilboa et al+, 1979), capped oligonucleotides cleaved from host mRNAs (Plotch et al+, 1981), or a polypeptide primer (Andino et al+, 1993) are used by reverse transcriptases, influenza, and poliovirus polymerase, respectively+ Utilization of the 39 end of a cleaved HDV RNA molecule as a primer for initiation of HDV replication may represent a similar situation in which RNA structural elements control recognition, specificity of cleavage (initiation) as well as the specificity and efficiency of template switching+ HDV and viroids may share a similar pol II-mediated replication mechanism that requires common sequence/structure elements in the RNA (Branch & Robertson, 1984)+ The template used in this study is derived from the highly conserved, viroid-like region of HDV RNA (Lai, 1995)+ Identification of the Hepatitis Delta Interacting Protein A (DIPA), a human homolog of HDAg, led to the hypothesis that HDV evolved from a viroid-like RNA that acquired HDAg ORF as a result of pol II switching templates from a viroid ancestor to the cellular mRNA (Brazas & Ganem, 1996)+ Furthermore, sequence comparison of a number of viroid variants suggested that RNA template switching may frequently occur during viroid replication (Hammond et al+, 1989;Koltunow & Rezaian, 1989;Rezaian, 1990;Hernandez et al+, 1992;Kofalvi et al+, 1997)+ Notably, stem-loops present at both ends of viroid RNAs are directly implicated in template switching during viroid replication (Semancik et al+, 1994;Diener, 1995)+ Further studies are necessary to determine if a similar template switching may also occur during HDV RNA replication+ Alternatively, it is possible that in contrast to the initiation of HDV transcription observed in vitro, initiation of HDV replication in vivo proceeds by a mechanism that does not require RNA cleavage, but still depends on a specific recognition of the same AG HDV RNA element for de novo initiation by pol II+ In that case, the observed template cleavage could reflect suboptimal conditions of the in vitro reac...…”
Section: Implications For Hdv Rna Replication In Vivomentioning
confidence: 99%